2006
DOI: 10.4315/0362-028x-69.10.2417
|View full text |Cite
|
Sign up to set email alerts
|

Food Worker Hand Washing Practices: An Observation Study

Abstract: Improvement of food worker hand washing practices is critical to the reduction of foodborne illness and is dependent upon a clear understanding of current hand washing practices. To that end, this study collected detailed observational data on food worker hand washing practices. Food workers (n = 321) were observed preparing food, and data were recorded on specific work activities for which hand washing is recommended (e.g., food preparation, handling dirty equipment). Data were also recorded on hand washing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 14 publications
3
102
1
7
Order By: Relevance
“…This findings agrees with Green et al, 2007 that a chain of personal, social and workplace factors influences the practices of the food handler, and these factors need to be investigated in order for a change in behaviour to take place. 9 …”
Section: Discussionmentioning
confidence: 99%
“…This findings agrees with Green et al, 2007 that a chain of personal, social and workplace factors influences the practices of the food handler, and these factors need to be investigated in order for a change in behaviour to take place. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Food handling personnel plays important role in ensuring food safety throughout the chain of food production and storage (Adewunmi et al, 2014;Green et al, 2006). Mishandling and disregard of hygienic measures on the part of the food vendors may enable pathogenic organisms gain entry and in some cases survive and multiply insufficient numbers to cause illness in the consumer (Tivadar, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that most of the vendors who sell both raw and cooked food items are not regulated. They operate haphazardly without any monitoring of what they prepare and how they prepare it (Adewunmi et al, 2014;Green et al, 2006) . The knowledge of food handlers about the food borne infections and their safety practices is an important issue in the outbreaks of food borne infection (Fowora, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that improper food handler practices (e.g. inadequate hand washing, wearing the same gloves for extended periods of time, handling unwrapped RTE meats after handling raw meats without washing hands) may result in cross-contamination of RTE foods and account for approximately 97 percent of foodborne illnesses (Green et al, 2006;Lianou & Sofos, 2007;Neal, Binkely, & Henroid, 2012). Therefore, performing observations on the behavior of food handlers and changing incorrect behavior can improve the level of this indicator leading to a more advanced food safety management system but will also contribute to the developing of a food safety culture (Luning et al, 2009).…”
Section: Discussionmentioning
confidence: 99%